Polydatin activates the Nrf2/HO-1 signaling pathway to protect cisplatin-induced hearing loss in guinea pigs - Li, Dafei; Zhao, Haiyan; Xu, Piao; Lin, Qiongping; Zhao, Tingting; Li, Chubing; Cui, Zhong-Kai; Tian, Guangyong (Frontiers in Pharmacology, 2022)
Irreversible sensorineural hearing loss is one of the most common side effects after cisplatin treatment. Prevention and reversal of hearing loss caused by cisplatin are of great importance for cancer patients, especially children. Oxidative stress is an important cause of hearing loss resulted from cisplatin, unfortunately, there is no drug yet available that can completely prevent and reverse the ototoxicity from cisplatin. Polydatin (PD) possesses excellent antioxidant and anti-inflammatory effects, however, its role in the cisplatin-induced hearing loss has not been investigated. Herein, we have explored the preventive and therapeutic effects of PD on cisplatin-induced hearing loss and the possible underlying mechanisms. In the in vivo setting with guinea pigs, we have demonstrated that PD can reduce the threshold shift of auditory brainstem response (ABR) caused by cisplatin, promote the nuclear translocation of Nuclear factor erythroid-2 related factor 2 (Nrf2), increase the expression of Nrf2 and heme oxygenase-1 (HO-1), and thus reduce the loss of outer hair cells (OHCs). PD can ameliorate cisplatin-induced hearing loss through activating the Nrf2/HO-1 signaling pathway. This study provides a potential strategy for preventing and improving hearing loss resulted from cisplatin treatment in clinics.